2021
DOI: 10.1088/1361-6544/abd528
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Schrödinger–Langevin equation

Abstract: We solve the Schrödinger equation with logarithmic nonlinearity and multiplicative spatial white noise on R d with d ≤ 2. Because of the nonlinearity, the regularity structures and the paracontrolled calculus can not be used. To solve the equation, we rely on an exponential transform that has proven useful in the context of other singular SPDEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…In the mathematics community, this equation has not seen much interest yet, despite the presence of unusual nonlinear effects. In [10], the author has shown that in the focusing case (λ < 0) every well-prepared density function of the solution of equation (1.2) on R d converges to a Gaussian function weakly in L 1 (R d ), whose mass and center are uniquely determined by its initial data ρ 0 and u 0 , whereas in the defocusing case (λ > 0) every solution disperses to 0, with a slower dispersion rate than usual directly affected by the nonlinear Langevin potential 1 2i log (ψ/ψ * ). Still in the defocusing case, up to a space-time rescaling incorporating dispersive effects, the density ρ of every rescaled solution of equation (1.2) on R d also converges to a Gaussian function weakly in L 1 (R d ), a phenomenon which is reminiscent of the defocusing logarithmic Schrödinger equation [9] (corresponding to the case µ = 0 in (1.2)).…”
Section: Introductionmentioning
confidence: 99%
“…In the mathematics community, this equation has not seen much interest yet, despite the presence of unusual nonlinear effects. In [10], the author has shown that in the focusing case (λ < 0) every well-prepared density function of the solution of equation (1.2) on R d converges to a Gaussian function weakly in L 1 (R d ), whose mass and center are uniquely determined by its initial data ρ 0 and u 0 , whereas in the defocusing case (λ > 0) every solution disperses to 0, with a slower dispersion rate than usual directly affected by the nonlinear Langevin potential 1 2i log (ψ/ψ * ). Still in the defocusing case, up to a space-time rescaling incorporating dispersive effects, the density ρ of every rescaled solution of equation (1.2) on R d also converges to a Gaussian function weakly in L 1 (R d ), a phenomenon which is reminiscent of the defocusing logarithmic Schrödinger equation [9] (corresponding to the case µ = 0 in (1.2)).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, our notion of global weak solution has to be adapted to the d-dimensional case, as well as system (1.3), and we refer to [6] and [8] for some d-dimensional analogue of Definition 2.1.…”
mentioning
confidence: 99%
“…We recall (see [8]) that there exists a unique global solution τ ∈ C ∞ ([0, ∞)) to this nonlinear ODE, and that this solution remains uniformly bounded from below by a strictly positive constant. Plugging these expressions into the second equation of (3.2), we also get that…”
mentioning
confidence: 99%
See 2 more Smart Citations